O O PRINCÍPIO DA HOSPITALIDADE POR DERRIDA E O PLURALISMO CONSTITUCIONAL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article investigates pluralism as a republican principle, the basis of the Democratic Rule of Law, which represents, in a broad and anthropological sense, or the recognition of diversity. The principle also embraces widespread respect as minorities, using affirmative policies such as those that can consolidate material that is the subject of great social prejudice, often on the fringes of society. In addition, this seeks to equalize in all the population that has the right to live with their differences, being able to participate in policies and expose their ideas and opinions. From another angle, you might look for Derrida's study of the principle of hospitality, which represents a real openness to another, a moral receptivity to strangers, or a right to be received. It emphasizes the Derrida’s thought that a foreigner is a stranger or should be accepted, while preserving his strangeness. Finally, given these concepts, the present wishes to associate or pluralist principle as acceptance of another type of hospitality proposed by Jaqcues Derrida. For the elaboration, application or method of deductive abortion, part of general principles to obtain a specific understanding, using also the doctrinal and scientific practices.